"The wet bottom of the abyss": the beginnings of Picasso’s Blue Period through Tyto Alba’s "La vida" - Giuliana, Virginie (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The life and work of the celebrated painter Pablo Ruiz Picasso are closely linked, as has been demonstrated by critics who have approached his production from different points of view. The suicide of his friend Carles Casagemas was the trigger for the so-called “blue period”, the first major stage in the Malaga-born painter’s artistic career, which the cartoonist Tyto Alba deals within the graphic novel La Vida, published in 2016. In this study, I will analyse how the graphic novel sheds light not only on the history of a friendship through a rich documentation about Picasso and Casagemas, but also, through the intermediality, the comic becomes the vehicle of Picasso’s painting and a graphic testimony of the Franco-Spanish fin-de-siècle bohemia experienced by the two artists.